KEPEMIMPINAN INOVATIF SEBAGAI STRATEGI PENINGKATAN KUALITAS BERAGAMA MELALUI KONSTRUKSI KESALEHAN SOSIAL DI MAN PEMALANG - Untung Sultoni; Siti Hartinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the role of innovative leadership as a strategy to improve the religious quality of students through the development of social piety at MAN Pemalang (an Islamic senior high school in Pemalang, Indonesia). The research was conducted using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In the analysis phase, the need to enhance students’ religious quality – particularly in terms of social piety – was identified. An innovative leadership-based program was then designed and developed to foster kesalehan sosial (social piety) among students, which includes activities promoting compassion, community service, and Islamic social values. The program was implemented under the guidance of the school’s leadership, and its effectiveness was evaluated using pre-test and post-test measurements of students’ religious quality. Results show a significant improvement in students’ overall religious quality after the implementation of the program, with the social piety aspect showing marked enhancement. A paired-samples t-test indicated that the increase in the religious quality score was statistically significant (p < 0.01), demonstrating the effectiveness of the innovative leadership strategy. The study concludes that an innovative leadership approach focusing on building social piety can serve as an effective strategy to improve the quality of religious life among students. This approach aligns with the idea of holistic piety – balancing ritual devotion and social morality – which is crucial in modern religious education. The findings contribute to educational leadership practices in religious schools and suggest that school leaders who embrace innovation and moral values can positively impact students’ character and religious development.